Benjamin Disraeli letters: 1815-1834 - Disraeli, Benjamin, 1804-1881.; Gunn, J. A. W. (John Alexander Wilson), 1937-; Matthews, John Pengwerne, 1927-; Schurman, D. M. (Donald M.); Wiebe, M. G. (Melvin George), 1939- (Toronto : University of Toronto Press, 1982)
This volume includes 363 letters (many previously unpublished) from€Benjamkin Disraeli's€school boy days to his establishment in the Tory camp under the patronage of Lord Lyndhurst. Most prominent are Disraeli's letters to his sister, Sarah, with whom he corresponded frequently over several decades.
Cover; Contents; Acknowledgements; Introduction; Collection of the Letters; Letters 1815-1837; A Note on Annotation; Editorial Principles and Conventions; Headnote; Text; Annotations; Postmarks; Disraeli Chronology 1804-1834; Abbreviations; Chronological List of Letters 1815-1834; Letters; Appendix I: Political Notes 1831-2; Appendix II: Aide-Memoire 11-15 November 1834; Appendix III: The Mutilated Diary 1833-4; Index to Volume One; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; X; Y; Z.
Print version record.
JSTOR
Keywords: Prime ministers -- Great Britain -- Correspondence; Statesmen -- Great Britain -- Correspondence; Politicians -- Great Britain -- Correspondence; Hommes d'État -- Grande-Bretagne -- Correspondance; Politiciens -- Grande-Bretagne -- Correspondance; Politicians; Prime ministers; Statesmen; Great Britain; Personal correspondence